EVANGELICAL ASSOCIATIONS OF WOMEN AND YOUNG PEOPLE IN COLOMBIA, 1900-1955: BETWEEN UNITY AND FRAGMENTATION (Tzintzun, Revista de Estudios Históricos, 2024)
This article presents a characterization of evangelical woman and youngassociations in Colombia along the first middle of twentieth century, which servedlike a fundamental strategy of this religious option for get a space in the publicnational sphere and get a position from traditional heralds of hegemonic power,also for extend their ideas among the population. Through of “sociability” categoryaims to elucidate the grade of evangelical incidence during the period and theway in which their religious agendas got to permeating or been permeated byothers social camps like culture and politics.
Keywords: sociability; evangelicals; social incidence; evangelical press